Consultancy for Drafting national Standards for the Strategy Framework and workplan for the implementation of the Guyana Safe Schools Programme - UNICEF Guyana and Suriname (UNICEF Guyana and Suriname, 2018)
The national consultant will draft the Standards for the Strategy Framework and workplan for the implementation of the Guyana Safe Schools Programme that is in line with the Ministry of Education’s Child Friendly Schools (CFS) programme and the CDEMA led Caribbean Model Safe School Programme. The scope of this consultancy focuses on providing the MoE with standards for Guyana’s Safe School Programme that link directly to existing policies and strategies focusing on resilience building and emergency preparedness and response. The Standards for the Strategy Framework will be drafted by the consultant by: • Conducting a desk review of all existing relevant documents/ instruments in Guyana’s Education Sector relating to Disaster Risk Reduction, Emergency Preparedness and Response, and Sustainable Education for Development; • Conducting field tests/ consultations with students in schools in Regions 1, 2, 8 and 9; and compile feedback; • Draft a Guyana Standard for Safe Schools; • Finalize standards and set strategy for the rolling out of the programme; • Identify human and financial resources required . • Draft a monitoring tool for the Plan The key deliverable will be the Preparation and submission of Strategy Framework and workplan for the implementation of the Guyana Safe Schools Programme. The components will comprise of: • Inception Report- Report on Desk Review of all existing relevant documents/ instruments in Guyana’s Education Sector with an agreed work plan by Ministry of Education and UNICEF • Draft Report scoping standards- Draft of Standards and consultation strategy approved by Steering Committee for consultations with students, Conduct field tests/ consultations with students in schools in Regions 1, 2, 8 and 9; and compile feedback; Submit draft of Standards for final review by Steering Committee • Final Report- Finalisation of Standards approved by Steering Committee.
Keywords: safe schools programme